Approximate Controllability of the Degenerate System with the First-Order Term. (5th August 2015) - Du, Runmei
Abstract : We consider the approximate controllability of the degenerate system with the first-order term. The first-order term in the equation cannot be controlled by the diffusion term. The system is shown to be approximately controllable by constructing a control by means of its conjugate problem.